Ngalap Berkah Tradition (A Case Study of the Ritual of Visiting the Grave and Buka Luwur of Sunan Kudus’s Tomb) - Maulana, Iqbal (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This research attempts to analyze the form of acculturation between Islam and local culture in the tradition of ngalap berkah performed by the people of Kudus, Central Java and its surroundings. This research was conducted to find out how the acculturation between Islam and local culture in ngalap berkah and why they preserve the tradition of ngalap berkah. In this case, this research tries to use a anthropological approach to reveal the phenomenon of the buka luwur tradition. The anthropological approach model is based on data collected by the author through interviews, observations, and surveys. The data processing technique in this research is descriptive qualitative, namely data analysis is carried out simultaneously with data collection. The results of this study indicate that the acculturation between Islam and local culture in the tradition of ngalap berkah carried out by the people of Kudus and its surroundings there are three kinds, namely, ngalap berkah about pilgrimage ritual to the tomb of Sunan Kudus, ngalap berkah on the former luwur of Sunan Kudus’s tomb, and ngalap berkah on the distribution of sego berkat in the opening ceremony of Sunan Kudus’s tomb. This tradition is still practiced by the community because they believe that the rituals of pilgrimage and opening the tomb of Sunan Kudus have nuances of abundant blessings in their lives.